Experimental & analytical evaluation of knock characteristics of producer gas - Arunachalam, Aparna, author; Olsen, Daniel B., advisor; Marchese, Anthony, committee member; Sharvelle, Sybil E., committee member (Colorado State University. Libraries, 2010)
Amongst the popular gaseous bio-fuels is producer gas. Evaluation of knock properties of producer gas enhances efficient utilization of this renewable energy resource in an internal combustion engine. A literature review revealed that producer gas is formed from a set of combustion-reduction reactions in a gasifier and is typically composed of 18-20% H2, 18-20%CO, 2-3% CH4, 12% CO2 and 48-50%N2. It is seen that a production process where the combustion and reduction reactions are effectively separated yields a gas rich in hydrogen. Hence based on the production method and range in gas composition five different producer gas compositions are chosen for knock evaluation. Knock evaluation for gaseous fuels has been done by previous researchers using the Methane Number method. This method requires the use of a Cooperative Fuel Research (CFR) F2 engine installed in Colorado State University’s Engines and Energy Conversion Laboratory. It was seen that the methane number of producer gas ranged from 54-131. Further it was quantitatively evaluated that addition of CO2 increases the critical compression ratio while H2 decreases it. Overall, the effect of CO2 on changing the critical compression ratio was found to be over twice that of H2. It was attempted to evaluate the methane number of producer gas using chemical kinetics software CHEMKIN. A Methane Number evaluation process was developed using CHEMKIN’s internal combustion engine model. There were significant differences between model and experiment. Recommendations for future work are discussed.
Covers not scanned.
Keywords: Fuelwood -- Combustion; Spark ignition engines -- Alternative fuels -- Testing; Biomass gasification